Upade myā, naññʻ upade myā, ʻa minʻ ʻmyā, nhaṅʻ kre ññā khyakʻ myā (Nuiṅʻ ṅaṃ toʻ Ṅrimʻ vapʻ Pi prāʺ mhu Taññʻ chokʻ reʺ ʼA phvaiʻ, 1989)
Acts, rules, orders, martial law orders, and declarations promulgated by the State Law and Order restoration Council of Burma.